A Call for Research on Sex Offender Treatment Programs - Jones, Ashley C. T. (International journal of offender therapy and comparative criminology, 2019)
The effects of sex offender treatment programs have been addressed in the literature, but there are opportunities to expand research and potentially improve existing sex offender treatment programs. The Federal Bureau of Prison's Sex Offender Treatment Program gives offenders the opportunity to change their behavior by reducing criminality and recidivism, and receive transition services as offenders exit the prison system and reenter society. This program is evidence-based and utilizes landmark research in sex offender treatment, however there are a few details that may present limitations to the effectiveness of the treatment program within the Federal Bureau of Prisons. Entry requirements, such as literacy, cognitive, and remaining sentence requirements, as well as the treatment program environment, present opportunities for research to evaluate the effects of these variables on the convicted sex offender population.